What’s in it for citizen scientists? An Analysis of Participant Inclusivity in Citizen Science Projects in Advanced Physics Research [version 3; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Claudia Magdalena Fabian; Elisabeth Unterfrauner; Beatriz Garcia; Gary Hemming (Open Research Europe)
Citizen science projects optimise the democratisation of the production of scientific knowledge. In these initiatives, research processes do not rely solely on scientists’ but on citizens’ engagement, likewise with benefits on both sides. As previous work shows, the inclusivity perspective of citizen science projects might be viewed critically as some groups of citizens tend to be overrepresented in these initiatives while others are left out. This paper explores the claim of inclusivity and the citizens’ benefits based on four citizen science projects in the fields of astrophysics and particle physics on the citizen science platform Zooniverse. Besides a general engagement strategy, the citizen science projects addressed two groups specifically, the elderly and people with visual impairments. The claim for inclusivity is reflected in the analysis of citizens’ demographic variables as an indicator for accessibility of the research projects. We used a pre-post design with questionnaires on science attitudes, motivations, skills, self-efficacy, and knowledge to assess what citizen scientists gained from participating in the project. The demographic analysis of the data reveals that participants were quite heterogeneous and that people who feel that they belong to a group that is discriminated against are particularly motivated to participate in citizen science projects. In terms of benefits, the results indicate knowledge and scientific skills gains, but no changes on other evaluative dimensions. Their attitude towards science was, in general, already rather positive when joining the projects, thus not leaving much room for change. These results confirm the importance of and call for a diversified citizen science engagement strategy and show that even in citizen science projects where the citizens’ task is limited to classifying data lead to scientific knowledge and skills gains.